ChemInform Abstract: Sugar‐Based Monodentate Phosphoramidite Ligands for Cu‐Catalyzed Enantioselective Conjugate Addition to Enones. Issue 25 (3rd June 2013) - Bauer, Tomasz; Majdecki, Maciej; Jurczak, Janusz
Abstract Novel monodentate phosphoramidite ligands (I) based on amines derived from α‐D‐xylofuranose are synthesized and applied to the cuprous triflate‐catalyzed conjugate addition to acyclic and cyclic enones.